2022
DOI: 10.3389/fpls.2022.780335
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Seed Transmission of Xylella fastidiosa in Pecan (Carya illinoinensis)

Abstract: Pecan bacterial leaf scorch, caused by Xylella fastidiosa subsp. multiplex, is an economically significant disease of pecan with known detrimental effects on the yield of susceptible cultivars. In this study, endosperm was harvested from developing pecan seeds, and direct qPCR and sequencing were used to detect and confirm the presence of X. fastidiosa. DNA was isolated from mature seeds originating from seven trees, revealing a positivity rate up to 90%, and transmission of X. fastidiosa from infected seed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Fungicide treatment of pecan trees in orchards is a common practice where diseases such as scab negatively impact crop production. Seed-borne pathogens in other crops [ 30 ] are a common occurrence that negatively impact crop production. Since antibiotics are known to shift microbial communities in pecan [ 31 ], the effects that fungicide treatments may have on the microbial composition of maternal trees, and thus seed-to-seedlings, should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fungicide treatment of pecan trees in orchards is a common practice where diseases such as scab negatively impact crop production. Seed-borne pathogens in other crops [ 30 ] are a common occurrence that negatively impact crop production. Since antibiotics are known to shift microbial communities in pecan [ 31 ], the effects that fungicide treatments may have on the microbial composition of maternal trees, and thus seed-to-seedlings, should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Research on wheat ( Triticum aestivum C. Linnaeus) leaves and common bean ( Phaseolus vulgaris C. Linnaeus) leaves revealed a shift in relative fungal abundance of epiphytic and endophytic fungi after fungicide treatments [ 32 , 33 , 34 ]. As reported in the literature, transmission of microbial organisms from seed to seedling is a natural occurrence [ 30 , 35 , 36 , 37 ]. Thus, if a shift in microbial composition of the maternal plant occurs, the microbiome of the resulting seeds may in turn be altered due to the influence that maternal plants have in shaping seed microbiomes [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Once in the seed coat, Xanthomonas travels through the intercellular spaces and spreads throughout the tissue of the seed (Zaumeyer, 1930). Seed to seedling transmission of microorganisms has also been reported in pecans with Xylella fastidiosa (Cervantes et al, 2022). A study by Brinkerhoff and Hunter (1963), found Xanthomonas malvacearum to be present in the embryos and seed coats of cotton.…”
Section: Microbial Composition Analysis Of Pecan Seedlingsmentioning
confidence: 92%